(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the process of digitization of the educational system in Uzbekistan and considers the main factors affecting its development. Reforms carried out in the field of education in our country, including the introduction of digital technologies, aimed at improving the quality of the public education system, preparing students for a modern Information Society. On the basis of decrees and decisions of the president of the Republic of Uzbekistan, the necessary measures are taken to develop digital education. This article presents how digital educational resources, i.e. multimedia materials, interactive tools, and new learning technologies, can be effectively applied to students ’ learning process. The article also shows the potential to make students ’ learning techniques more effective by integrating digital technology into education, to introduce new pedagogical approaches, and to make the learning process more interactive. The role of teachers in the effective use of modern digital tools is also highlighted, as it is an important factor in preparing students for the future global digital society. The article shows the need to introduce modern technologies and develop pedagogical innovations, which are important in the formation of the digital future of the educational system of Uzbekistan.